2022
DOI: 10.1039/d2nr03617g
|View full text |Cite
|
Sign up to set email alerts
|

Carbothermal redox reaction in constructing defective carbon as superior oxygen reduction catalysts

Abstract: The defects can greatly promote the catalytic activity of the carbon-based electrocatalyst due to charge redistribution of the electroneutral π-conjugated structure. However, it is still a huge challenge to introduce...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…29 The relative ratio of D and G bands (I D /I G ) increases in the order: 30%CPCA-500 < 30%CPCA-700 < 30%CPCA-900, indicating that 30%CPCA-900 has a large number of defects, which may be ascribed to the formation of graphitic nitrogen and denitrogenation/deoxygenation at high temperatures. 30 It is important to reveal chemical structures of the aerogels for understanding the wettability and water transportation. Therefore, FTIR and X-ray photoelectron spectroscopy (XPS) were used to analyze functional groups and occurrence of heteroatoms in the aerogels.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 The relative ratio of D and G bands (I D /I G ) increases in the order: 30%CPCA-500 < 30%CPCA-700 < 30%CPCA-900, indicating that 30%CPCA-900 has a large number of defects, which may be ascribed to the formation of graphitic nitrogen and denitrogenation/deoxygenation at high temperatures. 30 It is important to reveal chemical structures of the aerogels for understanding the wettability and water transportation. Therefore, FTIR and X-ray photoelectron spectroscopy (XPS) were used to analyze functional groups and occurrence of heteroatoms in the aerogels.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As Figure d displays, all the Raman spectra of CPCAs have D and G bands arising from the disordered structure and ordered graphitic carbon in carbon materials, respectively . The relative ratio of D and G bands ( I D / I G ) increases in the order: 30%CPCA-500 < 30%CPCA-700 < 30%CPCA-900, indicating that 30%CPCA-900 has a large number of defects, which may be ascribed to the formation of graphitic nitrogen and denitrogenation/deoxygenation at high temperatures . It is important to reveal chemical structures of the aerogels for understanding the wettability and water transportation.…”
Section: Resultsmentioning
confidence: 99%
“…23). 91,100,105,106,128,130,131,[133][134][135]141,144,148,187,189,192,194,198,212,214,216,225,226,240,242,246,248,[253][254][255]257,258,263,267,287,289,290,295,308,314,322, As a backup battery, higher actual specic energy is expected to meet the needs of wearable devices; zinc-air batteries need a exible substrate and high-power output.…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 23 Performance of different type of catalysts in the zinc-air battery according to reports 91,100,105,106,128,130,131,[133][134][135]141,144,148,187,189,192,194,198,212,214,216,225,226,240,242,246,248,[253][254][255]257,258,263,267,287,289,290,295,308,314,322,. …”
mentioning
confidence: 99%
“…Therefore, defect engineering is equally indispensable for enhancing the catalytic activity of SACs. 86,87 The actual catalysts may contain a large number of defects, and it has been shown that appropriate defects enhance the ORR performance of the catalysts. 88 Yuan et al 89 devised the decarboxylationinduced defect strategy for the preparation of defect-rich Co SACs.…”
Section: The Impacts Of Defect Engineeringmentioning
confidence: 99%